ACCOUNTING FOR REPOSSESSIONS AND TRADE-INS. - Hartman, David (The Accounting Review, 1939)
This article discusses the accounting practice for repossession and trade-ins in automobile industries. It describes that in automobile accounting the used-car traded in and the possession require special consideration if operating statements and balance-sheet accounts are to mean anything. Car dealers find it necessary to borrow heavily on their inventory of cars. The usual procedure is to arrange with some finance company to advance up to 100% of the "blue-book" value of each car placed on the floor of the dealers showroom or on his lot. Used-car advances will probably be limited to 80% of "blue-book" value. The dealer signs what is known in the trade as a "flooring note," securing this note with title to the car, and receiving a trust receipt for the car. Under this arrangement the dealer may sell the car, but the finance company does not transfer title until the flooring note is paid, usually from the proceeds of the sale. It sometimes happens that the contract will not cover the flooring note since price reductions must sometimes be effected to move cars which have remained on the floor too long. Based on these consequences of second-hand cars, their reconditioning, and responsiveness, it is assumed that the used car presents accounting problems peculiar to automobile merchandising.